(untitled) (Journal of Contemporary Educational Policies and Practices, 2023)
This study investigates the anxiety frequency of students in English-medium instruction classes and its relationship with gender and English performance. The questionnaire was administered to 300 students in three universities in Central Vietnam. The follow-up interviews and classroom observations were conducted to obtain more insights into the research problems. The results revealed that the EMI students had moderate levels of anxiety. The most provoking causes of students’ anxiety were worries about making mistakes, inconfidence during speaking tasks and fears of negative judgment from peers and teachers. The analyses of the variables related to foreign language anxiety revealed a significant negative correlation between students’ foreign language anxiety levels and their English competence. No statistically significant relationship was found between male and female students. The study provides several pedagogical insights for curriculum designers, educators and teachers to improve the quality of English-medium instruction courses in the Vietnamese context.